If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9n + -18 = -3(1 + 3n) Reorder the terms: -18 + -9n = -3(1 + 3n) -18 + -9n = (1 * -3 + 3n * -3) -18 + -9n = (-3 + -9n) Add '9n' to each side of the equation. -18 + -9n + 9n = -3 + -9n + 9n Combine like terms: -9n + 9n = 0 -18 + 0 = -3 + -9n + 9n -18 = -3 + -9n + 9n Combine like terms: -9n + 9n = 0 -18 = -3 + 0 -18 = -3 Solving -18 = -3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 8(3x-2y)+4[(-3x)+4]= | | 30x+29-68= | | -4+5n=-49 | | 6n+4=u-11 | | -345=3-6(2+8r) | | 7x=10(x-24) | | 2(w-1)-4=4(w-1) | | 3(3x+2)=7x-2 | | -5r-5=25 | | 3v+8=8+3v+v | | -15+b=23 | | 9s-10=3s+10s+10 | | 2(w-1)=3(x-1) | | -3(a+2)=-26+a | | -4(-4+7v)-2=-7(1+3v) | | 5z+9=21 | | (9x+1)/(11x+5) | | 4x^3=x | | 14x-4=80 | | -4(7+7n)+6n=94 | | 2x=19.5 | | M-1.2=2.09 | | -5n=4(-1)+8 | | 2c-6=18 | | z+z-6-2=-2 | | h/18-16-14=24 | | 9x(2x-1)=5 | | 8(x+14)=192 | | -4(5-5x)=36-8x | | 7x-8x-8=x-11 | | 14+7+(-1)= | | 1/7n-5=80 |